Simetria de translação : identificando possíveis aprendizagens de alunos do 8º e 9º anos ao utilizar softwares e tarefas - Valereto, Graziele Bombonato Delgado (2018)
The use of technology in classes as a teaching resource into teaching and learning process and this effects on student and teacher?s roles has been discussed in Brazil since The 70?s. However, new technological resources have been created every day, and this is an area which is still developing. On the other hand, researchers show that when symmetry teaching is in elementary school, it?s just about the reflection symmetry, ignoring translation or rotation symmetry concepts. In this context, the study pointed out the use of softwares can help with the translation symmetry teaching. This investigation was a qualitative and interpretative research, and it used the Didatic Engineering methodology. The subjects in the research were seven students from elementary school (3 from 8?? grade and 4 from 9?? ?????), from a private school of Maringá, countryside of Paraná State. A didactic sequential with 19 tasks and a questionnaire with 12 questions were applied using the SimiS and GeoGebra softwares, totalizing six meets. The data were collected by audio and video recorded during the meets, a dairy notes, and the student?s answers registered about these tasks. They were analyzed through the Van Hiele theory about Geometry learning, and the Ponte (2005) tasks characterization. The main results were that the softwares were very important tools for the students learn about Translation symmetry, because they could visualize this concept and explore this properties, raise hypotheses and refute or validate it. SimiS was a good software to introduce these concepts and GeoGebra could be used to reinforce it. Only one of the seven students achieved the level three (informal deduction) of Van Hiele theory, meanwhile, the other six students reached the level two (analysis)